2016
DOI: 10.3892/ol.2016.4788
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence in situ hybridization analysis of the ALK gene in 2,045 non-small cell lung cancer patients from North-Western Spain (Galicia)

Abstract: Identification of anaplastic lymphoma receptor tyrosine kinase (ALK) gene rearrangements is a standard diagnostic test in patients with advanced non-small cell lung cancer (NSCLC). The current study describes the experience of ALK rearrangement detection of a referral center in the public health care system of Galicia in North-Western Spain. The fluorescence in situ hybridization (FISH) patterns of the ALK gene and the clinical and pathological features of these patients are reported. This study is also of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…ALK gene rearrangements are seen in 1.9-6.8% cases of NSCLCs (6). The most common ALK gene rearrangement effusion was found to be higher in patients with ALK gene rearrangement as seen in the previous studies; however, this was not statistically significant (18,19).…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…ALK gene rearrangements are seen in 1.9-6.8% cases of NSCLCs (6). The most common ALK gene rearrangement effusion was found to be higher in patients with ALK gene rearrangement as seen in the previous studies; however, this was not statistically significant (18,19).…”
Section: Discussionmentioning
confidence: 42%
“…Anaplastic lymphoma kinase (ALK), is a tyrosine kinase receptor, encoded by the ALK gene. ALK gene rearrangements are seen in 1.9-6.8% cases of NSCLCs (6). The most common genetic rearrangement involves the echinoderm microtubule associated protein-like 4 (EML4) and ALK leading to formation of the EML4-ALK fusion gene that encodes for a chimeric protein with intrinsic tyrosine kinase activity.…”
Section: Introductionmentioning
confidence: 99%
“…Endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA), as an alternative to mediastinoscopy, is a minimally invasive procedure that integrates real‐time evaluation during bronchoscopy and sampling of mediastinal and pulmonary hilar lymph nodes and parenchymal masses in patients with advanced NSCLC for morphologic diagnosis, staging, and molecular analysis . Several studies, which are summarized in Table , have demonstrated that cell blocks obtained by EBUS‐TBNA can be reliably used for ALK FISH testing; indeed, informative results were obtained in greater than 90% of cases, and the rearrangement detection rate was similar (3.9%) to that of surgical specimens (3.4%) …”
Section: Alk Rearrangement Detection Techniquesmentioning
confidence: 99%
“…In the 1 discordant case, an ALK rearrangement was detected on the direct smear, and RT-PCR confirmed the rearrangement. 32 Accordingly, FISH performed using cytologic smears provides information about ALK status in most cases, 33,34 and FISH positivity on cytology reliably predicts tumor response. 35 Indeed, of the 9 ALK FISH-positive patients who received crizotinib treatment, 8 (88.9%) exhibited tumor regression.…”
Section: Alk Fish Testing On Cytologic Slidesmentioning
confidence: 99%
“…In the last two decades the treatment of NSCLC has been revolutionized by the emergence of molecular-driven targeted therapies such as small molecule tyrosine kinase inhibitors and immunotherapy, which has led to greatly increased survival and quality of life in selected patients. Since its identification in 2007 [4], translocations of the anaplastic lymphoma kinase (ALK) gene, which lead to activation of the ALK tyrosine kinase domain and oncogenesis, have been identified in approximately 3-6 % of all NSCLC cases [5][6][7][8][9]. Patients with NSCLC driven by ALK rearrangements may benefit from ALK tyrosine kinase inhibitor (TKI) therapies [10].…”
Section: Introductionmentioning
confidence: 99%